2020
DOI: 10.3390/nu12061587
|View full text |Cite
|
Sign up to set email alerts
|

Citrus aurantium L. Dry Extracts Ameliorate Adipocyte Differentiation of 3T3-L1 Cells Exposed to TNFα by Down-Regulating miR-155 Expression

Abstract: Citrus aurantium L. dry extracts (CAde) improve adipogenesis in vitro. These effects are dependent from an early modulation of CCAAT/enhancer-binding protein beta (C/Ebpβ) expression and cyclic Adenosine Monophosphate (cAMP) response element-binding protein (CREB) activation. C/Ebpβ and Creb are also targets of miR-155. This study investigated whether CAde regulates miR-155 expression in the early stages of adipogenesis and whether it ameliorates adipocyte differentiation of cells exposed to tumor necrosis fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Obesity is a state in which body fat is excessively accumulated and may cause social problems because of decreased quality of life and the development of chronic diseases. Many researchers have attempted to determine whether natural food materials are effective in preventing obesity by inhibiting adipogenesis [21][22][23][24]. Recent studies demonstrated the anti-obesity effects of extracts of Chrysanthemum indium and Chrysanthemum zawadskii in the Compositae family [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a state in which body fat is excessively accumulated and may cause social problems because of decreased quality of life and the development of chronic diseases. Many researchers have attempted to determine whether natural food materials are effective in preventing obesity by inhibiting adipogenesis [21][22][23][24]. Recent studies demonstrated the anti-obesity effects of extracts of Chrysanthemum indium and Chrysanthemum zawadskii in the Compositae family [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…All data are presented as mean ± standard deviation, and statistical calculations were performed using the t-test and ANOVA (one-way analysis of variance) with Bonferroni's multiple comparison tests. p < 0.05, p < 0.01, and p < 0.001 were used to indicate statistical significance [49][50][51].…”
Section: Discussionmentioning
confidence: 99%